Ecotoxicological Characterization of Lithium as a “Timebomb” in Aquatic Systems: Tadpoles of the South American Toad Rhinella arenarum (Hensel, 1867) as Model Organisms - Peltzer, Paola (2024)
The aim of this study was to evaluate the acute lethality and chronic sublethal effects of lithium (Li) on Rhinella arenarum tadpoles as model organisms. First a 96 h toxicity assay was performed by exposing tadpoles to Li concentrations from 44.08 to 412.5 mg L−1 to estimate the mortality, and lethal and sublethal effects. Another bioassay was carried out by exposing tadpoles to two environmentally relevant Li concentrations (2.5 and 20 mg L−1 ) for one and two weeks. The sublethal effects of Li on tadpoles were evaluated by analyzing biochemical, genotoxic, and physiological biomarkers. The mortality in Li-exposed tadpoles increased over time. The median lethal concentration (LC50) ranged from 319.52 (281.21–363.05) mg L−1 at 48 h to 66.92 (52.76–84.89) mg L−1 at 96 h. Exposure to Li at 2.5 and 20 mg L−1 induced alterations in enzymes related to detoxification, antioxidant, and hepatic mechanisms, endocrine disruption of thyroid hormones, genotoxicity, and effects on the physiology of the heart and gastrointestinal systems. Tadpoles exposed to the highest concentration in the chronic bioassay (20 mg L−1 Li), which is the concentration commonly recorded in Li mining sites, showed significant mortality after one week of exposure. These results warn about the high ecotoxicological risk of Li as a contaminant of emerging concern for amphibians.